Improvement of Operational Risk Measurement Accuracy on Power Plant Using Qualitative and Quantitative Method - Hani Wibieanto; Adithya Sudiarno (IPTEK Journal of Proceedings Series, 2019)
Implementation of maintenance programs in order to improve the performance of power plants required considerable cost, while existing funding sources are limited. Prioritization of maintenance program implementation based on risk level is needed to optimize the performance of power plant unit and maintenance cost required. The process of determining the level of risk can be done with qualitative and quantitative methods, each has advantages and disadvantages. This research compared accuracy of risk number on main equipment of power plant determined using qualitative method, quantitative methods and combined method which is the combination of weighted qualitative and quantitative risk number. Weight of qualitative risk is determined by the engineers in a focus group discussion (FGD) based on technology and capability criteria of equipment such as condition monitoring technology, warning system technology, ability to activate protection system, and load pattern of equipment, to improve the accuracy of risk measurement. Result from the calculations shows that risk number generated from the calculation using combined method has the closest average value and standard deviation to the actual loss